1959
DOI: 10.1152/ajplegacy.1959.197.5.1021
|View full text |Cite
|
Sign up to set email alerts
|

Physiological disposition of d- and l-thyroxine in the rat

Abstract: A comparison was made of the distribution and excretion of the optical isomers of thyroxine in the rat. d-Thyroxine disappeared more rapidly from the blood and was concentrated to a greater extent in the liver and kidney than was l-thyroxine. The concentration of d-thyroxine in such peripheral tissues as muscle, brain and skin was much less than the concentration of l-thyroxine. This difference in distribution to the peripheral tissues was of such magnitude as to suggest a possible basis for the different acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1962
1962
1990
1990

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…This difference may result from a greater depletion of liver glycogen stores (Table 1) and consequently more limited capacity for provision of glucose for the circulation. This would be compatible with the fact, that D-thyroxine is concentrated to a greater extent in the liver than L-thyroxine (Tapley et al 1959). The results support the view that the diffe¬ rences between L-thyroxine and D-thyroxine are only quantitative.…”
Section: Resultssupporting
confidence: 67%
“…This difference may result from a greater depletion of liver glycogen stores (Table 1) and consequently more limited capacity for provision of glucose for the circulation. This would be compatible with the fact, that D-thyroxine is concentrated to a greater extent in the liver than L-thyroxine (Tapley et al 1959). The results support the view that the diffe¬ rences between L-thyroxine and D-thyroxine are only quantitative.…”
Section: Resultssupporting
confidence: 67%
“…Other studies, in which the two isomers of thyroxine were not administered simultaneously into the same experimental subject, found that the metabolic disposal of D-thyroxine was much faster than its L-isomer (16,17). The early work of Sterling, Lashof, and Man (18) had shown that after a single injection of L-[3',5'-'"'IiT4, the biological half-life of serum radioactivity in euthyroid subjects varied with a range of 5-10 days.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that when administered parenterally, D-thyroxine is metabolized more rapidly and distributed differently than the L-isomer (19,20). In addition, the discrepancy between the potencies of these agents as measured in vivo and in vitro is not limited to the adenyl cyclase system (21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%